ANALISIS PENGGUNAAN MEDIA VIDEO ANIMASI PEMBELAJARAN MATERI RANTAI MAKANAN DILIHAT DARI MOTIVASI BELAJAR PADA PESERTA DIDIK DI JENJANG SD - Sevilla Putri Nuraini; Nanda Faradita , Meirza; Ichda Wahyuni , Holy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the use of animated video media in food chain learning on students' learning motivation at elementary school level. The research method used is descriptive qualitative with data collection techniques carried out through three main techniques, namely open questionnaires, interviews, and documentation. This study is shown through five main indicators, namely increasing students' attention and interest in the material as evidenced by their activeness during learning; ease in understanding complex concepts becomes simpler through animated visualization; growth of students' intrinsic motivation as seen from their interest in learning without coercion and high curiosity; active participation of students in the learning process such as asking questions, discussing, and completing assignments with enthusiasm; and increasing learning outcomes as an impact of the use of interesting and interactive media. The results of the study indicate that animated video media can encourage students' interest, attention, and understanding of the material. Animated videos are considered good at presenting abstract concepts such as food chains in an interesting and easy-to-understand way. This study describes that animated video media plays an important role in encouraging students' learning motivation.